Pengaruh Jamur Entomopatogen Rhizosfer Pertanaman terhadap Mortalitas Serangga Umpan Omphisa fuscidentalis (Lepidoptera: Pyralidae) di Laboratorium - Haperidah Nunilahwati; Yani Purwanti; Laili Nisfuriah; Frank Sinatra (Seminar Nasional Lahan Suboptimal, 2019)
Nunilahwati H, Purwanti Y, Nisfuriah L, Sinatra F.  2019. Effect of entomopathogenic fungi from the rhizosphere of plants on the mortality of insect bait omphisa fuscidentalis (Lepidoptera: Pyralidae) in laboratory. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal 2019, Palembang  4-5 September 2019. pp. 246-253. Palembang: Unsri Press. Entomopathogenic fungi are organisms that live as insect parasites and are used in environmentally friendly biological control in an effort to reduce the use of synthetic insecticides. The purpose of this study was to determine the effect of plant rhizosphere entomopathogenic fungi on O. fuscidentalis insect bait mortality in the laboratory. The results of the study can provide information about O. fuscidentalis insect larvae which can be used as bait entomopathogenic fungi for insects. Soil samples used to trap entomopathogenic fungi were taken by purposive sampling from the long bean crop rhizosphere in the Ogan Komering Ilir Regency. Fungi that infect bait insects are cultured in PDA media, incubated for 7 days and then identified. Mortality of bait insect larvae was observed at intervals of 3 days namely 3, 6, 9, 12 and 15 days after larval infestation in soil samples. The results showed the highest average mortality was on observation day 9 of 56% and lowest 0% on observation day 3. Entomopathogenic fungi that infect larvae of O. fuscidentalis bait insects were Beauveria bassiana and Metarhizium sp. O. fuscidentalis insect larvae can be used as bait insects for entomopathogenic fungi from rhizosphere of plants in the laboratory.Keywords: biological control, mortality, Omphisa fuscidentalis,  rizosphere